Study on Gas Permeation and CO2 Separation through Ionic Liquid Based Membranes with Siloxane-Functionalized Cations - Tome,LC; Gouveia,ASL; Ab,Ranii MA; Lickiss,PD; Welton,T; Marrucho,IM (Industrial & Engineering Chemistry Research, 2017)
This work explores ionic liquid-based membranes with siloxane functionalized cations using two different approaches: supported ionic liquid membranes (SILMs) and poly(ionic liquid)–ionic liquid (PIL–IL) composite membranes. Their CO2, CH4, and N2 permeation properties were measured at T = 293 K with a trans-membrane pressure differential of 100 kPa. The thermophysical properties of the synthesized siloxane-functionalized ILs, namely viscosity and density (data in the Supporting Information), were also determined. Contrary to what was expected, the gas permeation results show that the SILMs containing siloxane-functionalized cations have CO2 permeabilities that are lower than those of their analogues without the siloxane functionality. The addition of siloxane-based ILs into PILs increases both CO2 permeability and CO2/N2 permselectivity, although it does not significantly change the CO2/CH4 permselectivity. The prepared membranes present very diverse CO2 permeabilities, between 57 and 568 Barrer, while they show permselectivities varying from 16.8 to 36.8 for CO2/N2 and from 9.8 to 11.5 for CO2/CH4. As observed for other ILs, superior CO2 separation performances were obtained when the IL containing [C(CN)3]− is used compared to that having the [NTf2]− anion.